World Election History and Uzbekistan - Abdugaffarovich, Yuldashev Otabek (International Journal of Psychosocial Rehabilitation, 2020)
In this article, a comparative analysis of the electoral history of the countries of the world with Central Asia, that is, the formation of elections in the territory of Turkestan was made. It compares the formation of the electoral system, the electoral process, the requirements for elections, the rights of voters. It was also studied the requirements of the elections in Turkestan, as well as the formation of the elections in Uzbekistan before independence, and based on scientific sources.